Stability Phenotypic Characters and The Scent of Gama Melon Parfum Cultivar - Sigit Dwi Maryanto; Rini Etika Ranis; Budi Setiadi Daryono (Institut Teknologi Sepuluh Nopember, 2014)
Parfume is one of the cosmetic product and its use is consistent. High prices of cosmetic product cause dependence on imported product. Innovative research is needed to reduce dependence on imported product. Melon is one of the potential horticultural crops to be developed in plant breeding. Gama Melon Parfum cultivars has strong of fragnant so its potentially to be used as parfume material. Research on morphological characters to support of Gama Melon Parfum as superior cultivar. The research aims to determine the level of stability of phenotypic characters and aroma of melon Gama Melon Parfum cultivar. Research methods was cultivated Gama Melon Parfum in Kebun Pendidikan Penelitian dan Pengembangan Pertanian (KP4) UGM Yogyakarta. Furthermore, the phenotypic characters was observed consist of qualitative and quantitative characters. The methods of sampling used Randomize Complete Block Design (RCBD) and quantitative phenotypic characters were analyzed using software PKBT-STAT-2. The result of qualitative characters on Gama Melon Parfum cultivars has oblate shape, small size, yellow-orange skin of colour with 9-10 lobes and longitudinal, white of flesh colour, crunchy texture, bitter taste, zero score of nett (not netted), strong of fragnant, and has spesific qualitative characters called turbin. Quantitative characters on Gama Melon Parfume cultivars consist of average weight of 160 gram; circumference of 21,8 cm; horizontal diameter of 6,89 cm; vertical diameter of 6,44 cm; thick skin of 1 mm, thick flesh of 1,06 cm; the number of seed of 200-300; weight of 100 seed of 1,74 gram; harvest 63-65 day after cultivate; and 17 days of storage time.